NorthStar. - Mills, Robin 1962-; Frazier, Laurie (Longman, 2004)
Explore fascinating content while building language competence and critical thinking skills. The best-selling NorthStar series (Series Editors: Frances Boyd and Carol Numrich), now in its Second Edition, offers two strands: a reading and writing strand and a listening and speaking strand. Both strands stimulate students' imagination, encourage critical thinking, and promote personal expression.